2020
DOI: 10.21873/invivo.12011
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic vs. Open Surgery for Stage II/III Colon Cancer Patients With Body Mass Index >25 kg/m2

Abstract: Aim: To compare long-and short-term outcomes of laparoscopic surgery with those of open surgery for patients with colorectal cancer and body mass index over 25 kg/m 2. Patients and Methods: This multicentre, retrospective study analysed clinical records and identified 178 patients with body mass index over 25 kg/m 2 who underwent surgery for colon and rectosigmoid cancer between 2000 and 2016. After applying propensity score matching, 96 patients were finally included. The primary outcome was the 3-year recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Moreover, an interrelationship has been demonstrated between obesity and increased postoperative adverse events, such as readmission, reintervention, and mortality [ 12 , 14 , 15 ]. These events are partially due to the higher occurrence of cardiopulmonary comorbidities and wound healing disorders in obese subjects [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an interrelationship has been demonstrated between obesity and increased postoperative adverse events, such as readmission, reintervention, and mortality [ 12 , 14 , 15 ]. These events are partially due to the higher occurrence of cardiopulmonary comorbidities and wound healing disorders in obese subjects [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to Asian patients, previous reports also revealed preferable outcomes for LAC, even for patients with BMI ≥25 kg/m 2 who have more comorbidities 9,10,13 . Furthermore, these studies have also reported relatively lower conversion rates (3.1% to 4.0%) than previously reported (14% to 45%) 9,10 . One possible explanation for this discrepancy is that the lower conversion rates were reported by specialized high‐volume centers.…”
Section: Discussionmentioning
confidence: 87%
“…However, recent retrospective studies have revealed that LAC performed in obese patients is acceptable in terms of operation time, estimated blood loss, postoperative complications, and recovery time 28,29,30 . With regard to Asian patients, previous reports also revealed preferable outcomes for LAC, even for patients with BMI ≥25 kg/m 2 who have more comorbidities 9,10,13 . Furthermore, these studies have also reported relatively lower conversion rates (3.1% to 4.0%) than previously reported (14% to 45%) 9,10 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations